2022
DOI: 10.33394/jollt.v10i2.4826
|View full text |Cite
|
Sign up to set email alerts
|

A Multilingual Turn: Translanguaging by Design Activity in an Efl Context

Abstract: Translanguaging can be the latest all-embracing approach in language policy and assessment needed to substitute previous linguistic practices that treated languages as separate entities in a globalised world. This study is based on translanguaging by analysing activities that involved two cartoons in a multilingual classroom. This research was conducted to determine the opinions of Grade 12 EFAL learners on translanguaging by design activity in a multilingual setting. Grade 12 EFAL were chosen for their rich e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For Li (2018) and Van Viegen and Zappa-Hollman (2019), the focus on plurilingualism and translanguaging pedagogies is to bring out multiple modalities and the use of different semiotic tools such as language and technology to be integrated into classroom practices such that all communicative experiences learners bring to class are used to gain new knowledge. Zano (2022) concurs that translanguaging and pluralistic strategies are tools that empower learners to use their pre-existing linguistic knowledge to explore new given tasks, thus taking ownership of the learning process. For example, the above can be achieved through code-switching strategies, where the teacher temporarily alternates between languages to aid learning as Cheng (2015) found that code-switching between L1 and L2 motivated learners and helped them to understand the conversation, particularly if the strategy was accompanied by visual aids, such as pictures and short videos which were related to learners' lived experiences.…”
Section: Introductionmentioning
confidence: 83%
“…For Li (2018) and Van Viegen and Zappa-Hollman (2019), the focus on plurilingualism and translanguaging pedagogies is to bring out multiple modalities and the use of different semiotic tools such as language and technology to be integrated into classroom practices such that all communicative experiences learners bring to class are used to gain new knowledge. Zano (2022) concurs that translanguaging and pluralistic strategies are tools that empower learners to use their pre-existing linguistic knowledge to explore new given tasks, thus taking ownership of the learning process. For example, the above can be achieved through code-switching strategies, where the teacher temporarily alternates between languages to aid learning as Cheng (2015) found that code-switching between L1 and L2 motivated learners and helped them to understand the conversation, particularly if the strategy was accompanied by visual aids, such as pictures and short videos which were related to learners' lived experiences.…”
Section: Introductionmentioning
confidence: 83%
“…Studies have revealed that translanguaging has several advantages in an additional language context (Sefotho 2022, Zano 2022a). According to Zhou and Landa (2019), translanguaging emphasises dialogic learner-centred instruction that always puts the learner first.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Helping students bring to mind prior knowledge can have a strong positive impact on learning. Similarly, helping students relate new information from peers to the knowledge that they already have aids them to understand and organise information in meaningful ways (Zano 2022a;Zano 2022b;Zano 2020a;Zano 2020b). The respondents noted thus:…”
Section: When Teachers Allow Learners To Use Their Home Languages In ...mentioning
confidence: 99%
“…However, recent translanguaging literature has paid attention to teachers' deployment of multiple linguistic resources for scaffolding. The findings of the studies (e.g., Zano, 2022;Zano, 2021;Zano, 2010;Vogel & Garcia, 2017) typically indicate that the teachers encourage learners to draw on their multilingual and multimodal resources in the classroom, which consequently can facilitate the learners' development of multilingualism.…”
Section: Literature Reviewmentioning
confidence: 99%